2003
DOI: 10.1073/pnas.1933744100
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 is a marker of aggressive breast cancer and promotes neoplastic transformation of breast epithelial cells

Abstract: The Polycomb Group Protein EZH2 is a transcriptional repressor involved in controlling cellular memory and has been linked to aggressive prostate cancer. Here we investigate the functional role of EZH2 in cancer cell invasion and breast cancer progression. EZH2 transcript and protein were consistently elevated in invasive breast carcinoma compared with normal breast epithelia. Tissue microarray analysis, which included 917 samples from 280 patients, demonstrated that EZH2 protein levels were strongly associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

72
1,354
11
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,501 publications
(1,446 citation statements)
references
References 33 publications
72
1,354
11
9
Order By: Relevance
“…PcG protein expression is often dysregulated in several types of cancer and strongly correlates with an invasive and/or metastatic phenotype [119,120]. Bmi-1 (PcG protein B lymphoma Mo-MLV insertion region 1 homolog), was initially identified as an oncogene cooperating with c-myc in the development of murine pre-B-cell lymphomas [121].…”
Section: Bmi-1mentioning
confidence: 99%
“…PcG protein expression is often dysregulated in several types of cancer and strongly correlates with an invasive and/or metastatic phenotype [119,120]. Bmi-1 (PcG protein B lymphoma Mo-MLV insertion region 1 homolog), was initially identified as an oncogene cooperating with c-myc in the development of murine pre-B-cell lymphomas [121].…”
Section: Bmi-1mentioning
confidence: 99%
“…EZH2 is over-expressed in breast cancer compared with normal breast epithelia and expression is associated with invasiveness, increased proliferation, markers of an aggressive phenotype (basal or HER2 positive) and reduced survival outcomes [1,3,6,17,28]. Overexpression of EZH2 in immo rtalized mammary epithelial cell lines promotes anchorage independent growth and cell invasion and EZH2 over-exp ressing cells are tu morigenic when injected into mammary fat pads of nude mice [4,17].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of EZH2 in immo rtalized mammary epithelial cell lines promotes anchorage independent growth and cell invasion and EZH2 over-exp ressing cells are tu morigenic when injected into mammary fat pads of nude mice [4,17]. Furthermore EZH2 is required for embryonic stem cell survival and deletion is embryonic lethal [25].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigators have reported that EZH2 is overexpressed in aggressive prostate cancer, 21 breast cancer, 22 bronchial squamous cell cancer, 19 melanoma, 23 bladder cancer, 24 liver cancer, 25 and gastric cancer. 26 EZH2 expression levels correlate with aggressiveness, metastasis, and a poor prognosis.…”
mentioning
confidence: 99%
“…26 EZH2 expression levels correlate with aggressiveness, metastasis, and a poor prognosis. [21][22][23] However, to our knowledge, there have been no studies evaluating EZH2 expression and its correlation with clinical and clinicopathologic features in a large cohort of patients with NSCLC.…”
mentioning
confidence: 99%